Against Captivity: Black Girls and School Discipline Policies in the Afterlife of Slavery. (January 2016) - Wun, Connie
Multilayered disciplinary policies including sophisticated surveillance mechanisms and harsh punitive practices increasingly characterize schools in the United States. Researchers contend that these modalities funnel students into prisons and produce "prison-like" conditions and/or militarized spaces. Most studies have examined the effects of these school policies and practices on boys of color, particularly Black boys. Although these frameworks are useful, they obscure the relationship that school discipline policies have to Black girls and violence. Based on a 12-month case study of a high school in northern California, "Against Captivity: Black Girls and School Discipline in the Afterlife of Slavery, " finds that through formal discipline policies and informal punitive practices, Black girls' are subject to constant surveillance while their lives are perpetually disavowed. This article contends that school discipline policies position Black girls as "captive objects." The girls are under constant surveillance while they are refused access to agency, autonomy, and self-defense against multiple forms of violence including gratuitous punishment inflicted by school faculty.